The Girl Who Never Made Mistakes - Pett, Mark.; Rubinstein, Gary. (Naperville, Ill. : Sourcebooks Jabberwocky, 2011)
Beatrice is so well-known for never making a mistake that she's greeted each morning by fans and reporters, but a near-error on the day of the school talent show could change everything.
Keywords: Perfectionism (Personality trait) -- Juvenile fiction; Self-confidence -- Juvenile fiction; Anxiety -- Juvenile fiction; Talent shows -- Juvenile fiction; Perfectionism (Personality trait) -- Fiction; Self-confidence -- Fiction; Anxiety -- Fiction; Talent shows -- Fiction